Age-dependent variations in rumen bacterial community of Mongolian cattle from weaning to adulthood - Ahmad, A.A.; Zhang, J.; Liang, Z.; Du, M.; Yang, Y.; Zheng, J.; Yan, P.; Long, R.; Tong, B.; Han Jianlin; Ding, X. (Springer, 2022)
Rumen microbes play an important role in ruminant energy supply and animal performance. Previous studies showed that the rumen microbiome of Mongolian cattle has adapted to degrade the rough forage to provide sufficient energy to tolerate the harsh desert ecological conditions. However, little is known about the succession of rumen microbes in different developmental stages of post-weaning Mongolian cattle.Here, we examined the succession of the rumen microbial composition and structure of 15 post-weaning Mongolian cattle at three developmental stages i.e., 5 months (RM05), 18 months (RM18) and, 36 months (RM36) by using the 16S rRNA gene sequencing method.We did not find any age-dependent variations in the ruminal concentrations of any volatile fatty acid (VFA) of Mongolian cattle. The diversity of the rumen bacterial community was significantly lower in RM05 group, which reached to stability with age. Bacteroidetes and Firmicutes were the two dominant phyla among all age groups. Phylum Actinobacteria was significantly higher in RM05 group, phyla Spirochaetes, and Tenericutes were highly abundant in RM18 group, and phyla Proteobacteria and Epsilonbacteraeota were enriched in RM36 group. Genera Prevotella_1, Bacteroides, and Bifidobacterium were abundant in RM05 group. The short chain fatty acid (SCFA) producing bacteria Rikenellaceae_RC9_gut_group showed high abundance in RM18 group and fiber degrading genus Alloprevotella was highly abundant in RM36 group. Random forest analysis identified Alloprevotella, Ileibacterium, and Helicobacter as important age discriminatory genera. In particular, the genera Ruminococcaceae_UCG-005, Bacteroides, Saccharofermentans, and Fibrobacter in RM05, genera [Eubacterium] coprostanoligenes_group, Erysipelotrichaceae_UCG-004, Helicobacter, Saccharofermentans, Papillibacter, and Turicibacter in RM18, and genera Rikenellaceae_RC9_gut_group, Lachnospiraceae_AC2044_group, and Papillibacter in RM36 showed the top interactions values in the intra-group interaction network.The results showed that rumen microbiota of Mongolian cattle reached to stability and maturity with age after weaning. This study provides some theoretical evidence about the importance of functional specific rumen bacteria in different age groups. Further studies are needed to determine their actual roles and interactions with the host.